Irradiation of mung beans (Vigna radiata): A prospective study correlating the properties of starch and grains - Castanha N. (2019)
Cienciactiva from the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica” (CONCYTEC, Peru) for the A.C. Miano Ph.D. scholarship (Contract 272-2015 - FONDECYT);